Mort et résurrection du capitalisme libéral, Death and Resurrection of Liberal Capitalism - Laval, Christian (Revue du MAUSS, 2007)
Pour comprendre La Grande Transformation de Karl Polanyi, il faut la replacer dans le contexte des années 1930 et 1940, époque de contestation générale du vieux libéralisme « manchestérien ». L’article compare les positions de quatre auteurs contemporains : Karl Polanyi, Joseph Schumpeter, Friedrich von Hayek et Walter Eucken. Cette comparaison montre d’abord que Polanyi n’était pas le seul à constater la fin du cycle libéral du capitalisme. Elle montre ensuite que la question portait aussi sur le type d’intervention de l’État. La nouveauté introduite par le néolibéralisme réside dans le fait que le marché n’est pas une nature, mais un ordre politiquement construit., ENG: To have an accurate reading of Karl Polanyi’s The Great Transformation, the reader should put his work back in its context of the 1930’s and 1940’s, in a time of widespread criticism of the old « manchesterian » liberalism. The text draws a parallel between the points of view of four contemporary writers : Karl Polanyi, Joseph Schumpeter, Friedrich Von Hayek et Walter Eucken. First and foremost, it shows that Polanyi was not the only writer to note the end of the liberal cycle of capitalism. Then, it emphasizes the fact that the debate was focused on the type of state intervention. The originality brought about by neoliberalism lies in the conception of market, which is no more considered as natural but as a political construction.
Sociology
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; SCHUMPETER; Joseph Alois; 1883-1950; liberal capitalism; neoliberalism